Concurrent Sphingomonas paucimobilis and Mycobacterium tuberculosis Meningitis in an Immunocompromised Patient: A Rare Case Report and Comprehensive Review of Literature - Iosif Marincu; Felix Bratosin; Iulia Bogdan; Catalin Dumitru; Carmen Nicoleta Stoica; Andrei Nicolae Csep; Narcisa Mederle; Roxana Manuela Fericean; Alexandru Ovidiu Mederle; Reshmanth Prathipati; Gratiana Nicoleta Chicin; Adelina Mavrea; et al. (Medicina, 2023)
Sphingomonas paucimobilis is a gram-negative bacillus that is widely distributed in the environment but rarely causes infections in humans. Meningitis caused by S. paucimobilis is an extremely rare clinical entity with very few reported cases in the literature. The clinical presentation and management of S. paucimobilis meningitis are not well established, and further research is needed to better understand this rare infection. Therefore, the goal of this study was to present probably the only case of meningitis caused by co-infection with S. paucimobilis and Mycobacterium tuberculosis and to describe the diagnostic and therapeutic challenges encountered, in correlation with the other very few reported cases of S. paucimobilis meningitis. A 64-year-old male farmer residing in a rural area was admitted with symptoms of severe headache, somnolence, and confusion. He had several comorbidities, including adrenal insufficiency, duodenal ulcer, and hypercholesterolemia. Lumbar puncture showed elevated leukocyte counts, glucose, and a marked rise of cerebrospinal fluid (CSF) proteins, indicating bacterial meningitis, which was confirmed by CSF culture that isolated S. paucimobilis and Mycobacterium tuberculosis. Antituberculosis therapy was initiated with isoniazid (300 mg/day), rifampicin (600 mg/day), pyrazinamide (2000 mg/day), and streptomycin (1 g/day). Ceftriaxone was introduced nine days later, after CSF culture grew S. paucimobilis, and was discharged without complications after 40 days of hospitalization. The literature search revealed a total of 12 published cases of S. paucimobilis meningitis in patients ranging from two months old to 66 years old. Among these cases, eight (66%) reported a favorable outcome, while two (17%) cases resulted in a poor outcome, and two (17%) were fatal. It was observed among the 13 identified cases (including ours) that the CSF white blood cell count had an average of 178.9 × 103/mm3, an average glucose level of 33.0 mg/dL, and an average protein count of 294.2 mg/dL. Most cases improved appropriately under antibiotic therapy with intravenous ceftriaxone, Meropenem, and Vancomycin. In conclusion, although extremely rare, S. paucimobilis meningitis has good outcomes even in immunocompromised patients with appropriate antibiotic therapy and close monitoring, while the diagnosis should not be excluded even in immunocompetent patients.